Strategi Bisnis Ditinjau dari Perspektif Etika Bisnis Syariah pada Toko Agoeng Cell di Pondok Gede Jakarta Timur - Naufal Mufid Ramli; Yenty Astarie Dewi (ARZUSIN, 2026)
Although MSME business strategies in the cellular retail sector have received attention in several previous studies, research that specifically integrates business strategy analysis with the perspective of sharia business ethics remains limited. This study aims to analyze business strategies and evaluate their implementation from the perspective of sharia business ethics at Toko Agoeng Cell. This study used a qualitative approach with a case study design, involving 37 participants consisting of 7 key informants, namely the owner and employees, and 30 customers selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using qualitative descriptive analysis and a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. The results showed that Toko Agoeng Cell experienced a decline in sales during the 2020–2023 period due to increasing competition and changes in consumer behavior toward digital channels, before experiencing an increase in 2024. The SWOT analysis showed that the dominant strategy was the SO (Strengths–Opportunities) strategy, namely utilizing internal strengths in the form of affordable prices, good service, and customer trust to capture digital market opportunities. The implementation of sharia business ethics was reflected in the practices of honesty and service, but it had not been systematically integrated into the business strategy. These findings contribute to the development of value-based business strategy studies and expand understanding of the integration of strategic management and sharia business ethics in the MSME context. The conclusion of this study emphasizes the importance of adaptive, structured, and sharia ethics-based business strategies to improve the competitiveness of cellular retail MSMEs.